A framework for assessing and managing dependencies in corporate transition plans - Adrien Rose; Gireesh Shrimali; Krista Halttunen (iScience, 2025)
Summary: The urgency of mitigating climate change has increasingly driven companies to develop corporate climate transition plans (CTPs). Factors beyond the direct control of a company can significantly influence the successful implementation of CTPs, but this issue is not addressed comprehensively by existing scientific literature or CTP assessment frameworks. This article introduces the concept of transition plan dependencies, highlighting the necessity of considering external factors such as economic trends, technological advancements, policy environments, and sectoral transitions. Through a combination of a systematic literature review and semi-structured interviews, we propose frameworks and metrics for identifying, quantifying, and managing these dependencies. We use sectoral examples to illustrate the framework and quantification methods, and we suggest next steps to improve the analysis and the management of dependencies in corporate transition plans. This article aims to serve as a foundation for further academic research on transition plan dependencies and their practical applications.